Fabrication and optimization of gastro retentive drug delivery system with HPMC and polyethylene oxide (PEO) matrix - Senjoti, Faria Gias; Jaffri, Juliana Md.; Mandal, Uttam Kumar (2014)
Gastro retentive tablets of metformin HCl were prepared based on polymer swelling and gas formation. Combination of HPMC and polyethylene oxide was used as both matrix forming agent and swelling agent, while sodium bicarbonate as gas forming agent. Fabricated tablets were optimized by response surface methodology (RSM) utilizing Box Behnken experimental design. The optimized tablets were further characterized by surface morphology, drug release kinetics, accelerated stability study etc. The optimized tablets enabled to float for more than 24 h and sustained the drug release for 12 h.